The relationship of organizational factors in transfer of training at the workplace: a case study in SAJ Ranhill Sdn. Bhd. / Nur Aisyah Abdul Aziz - Abdul Aziz, Nur Aisyah (Faculty of Business and Management, 2018)
The purpose of this study is to investigate the relationship of organizational factors in the transfer of training at the workplace among employees. The organizational factors includes supervisor support, peer support, organizational support and opportunity to perform. This study was carried out among 289 employees at Syarikat Air Johor (SAJ) Ranhill Sdn. Bhd. The data for this study have been collected by using questionnaire. This research was conducted through distributing adapted questionnaire using convenience sampling method. Furthermore, the result of study shows that there is a significant relationship of supervisor support, peer support, organizational support and opportunity to perform towards transfer of training. Therefore, the researcher have hypothesized the relationship between the organizational factors and transfer of training.